2007
DOI: 10.1002/pd.1669
|View full text |Cite
|
Sign up to set email alerts
|

Isolated left‐sided congenital diaphragmatic hernia: cardiac axis and displacement before fetal viability has no role in predicting postnatal outcome

Abstract: This study does not support the hypothesis that objective assessment of mediastinal shift in fetuses with left-sided CDH has a role in predicting postnatal outcome before fetal viability, which is when it would be more useful for counseling patients regarding whether to continue with the pregnancy or to opt for termination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…This finding has been attributed to compression of the left atrium by herniated abdominal organs (mainly the liver), redistribution of fetal cardiac output, and/or low pulmonary venous return. Although left ventricular volumes are about one third smaller than in normal fetuses, cardiac shifting or dimensions do not predict postnatal outcome in fetuses with isolated left-sided congenital diaphragmatic hernia [116]. This finding is supported by the observation that cardiac dimensions are not related to significant changes in cardiac function (as measured by ejection fraction or MPI) [8] and by the fact that the growth of the heart generally catches up after surgical correction in the neonatal period and that cardiac size is normal in long-term survivors of isolated congenital diaphragmatic hernia [117].…”
Section: Research and Clinical Applications Of Fetal Cardiac Functionmentioning
confidence: 99%
“…This finding has been attributed to compression of the left atrium by herniated abdominal organs (mainly the liver), redistribution of fetal cardiac output, and/or low pulmonary venous return. Although left ventricular volumes are about one third smaller than in normal fetuses, cardiac shifting or dimensions do not predict postnatal outcome in fetuses with isolated left-sided congenital diaphragmatic hernia [116]. This finding is supported by the observation that cardiac dimensions are not related to significant changes in cardiac function (as measured by ejection fraction or MPI) [8] and by the fact that the growth of the heart generally catches up after surgical correction in the neonatal period and that cardiac size is normal in long-term survivors of isolated congenital diaphragmatic hernia [117].…”
Section: Research and Clinical Applications Of Fetal Cardiac Functionmentioning
confidence: 99%
“…Historically, the degree of left cardiac hypoplasia was indeed suggested to be a prognostic marker for neonatal morbidity and mortality . Later, this was challenged, and more recently, a large series by Vogel et al on 85 live‐born neonates with LCDH indeed confirmed the absence of correlation between the degree of left ventricular hypoplasia documented in utero and postnatal survival . Moreover, after surgical correction of the diaphragm, cardiac growth generally catches up, and in the majority of the long‐term survivors, cardiac size is normal …”
Section: Discussionmentioning
confidence: 99%
“…MRI is more reliable than ultrasound [37]. In two studies using two-dimensional ultrasonography, mediastinal (cardiac) shift was shown not to predict fetal viability in those with left-sided CDH [61]. A pleural and/ or a pericardial effusion in patients with diaphragmatic defects suggests an eventration of the diaphragm rather than a CDH [62,63].…”
Section: Antenatal Diagnosis Prognosis and Counsellingmentioning
confidence: 97%
“…The lung-to-thorax transverse area ratio (L/T ratio) has also been used to assess the degree of pulmonary hypoplasia [ [61,62] are being used to evaluate the developing fetus. Their use will increase as fetal surgery develops [37].…”
Section: Antenatal Diagnosis Prognosis and Counsellingmentioning
confidence: 99%